Framing and assessing classroom opportunity to learn: the case of Mexico. Issue 1 (2nd January 2016) - Jensen, Bryant; Pérez Martínez, María Guadalupe; Aguilar Escobar, Angélica
Abstract : Educational policy in Mexico and throughout Latin America is shifting focus from school access to school quality. Improving 'quality' is often interpreted as enhancing student learning opportunities, but three issues remain unresolved: (a) what constitutes opportunity to learn (OTL) in classrooms; (b) how to assess classroom OTL (COTL); and (c) how to address cultural and contextual differences. We synthesise international research to propose a framework of COTL, with implications for assessment and improvement. We discuss the case of Mexico, and identify three COTL elements: instructional time, generic quality and local quality. Instructional time addresses 'how much' opportunity children are provided to participate in classroom activities. Generic quality addresses 'how well' learning opportunities are delivered. And local quality – especially critical for rural and indigenous Mexican children – considers 'how meaningfully' opportunities are instantiated. We identify challenges and opportunities for COTL assessment, as well as their relevance to needed improvements.